Control Behavior through Self-Control in Islamic Education - Suhartini, Andewi; Nursobah, Asep; Hayati, Tuti; Yulianingsih, Yuyun (International Journal of Engineering and Technology, 2018)
Islam views, everyone has the potential to be good and bad that can be actualized in positive and deviant behaviors. Islamic education is a process that converts bad to good the potential actualized in good behavior. There are some efforts that can make a person behave positively, namely self-control, habituation, and the creation of environments. Among all these three things, restraint should be most significant. This article aims to describe the effort to control behavior through self-control in the process of Islamic education. It is based on the assumption that a person’s behavior, including teenagers, is the embodiment of knowledge and attitude he had. Meaning and appreciation of the knowledge and experience of one’s life became the main controller for the behavior. It took a concrete means of control either heard or seen to make a person have self-control. In the process of Islamic education, the control devices are in the form of good advice approach (mau’izhah hasanah), and a set of good examples (uswah hasanah). Advice heard and interpreted can motivate a person to follow. A figure or a model can be viewed and interpreted to encourage someone to follow. This is the essence of self-control of one’s behavior. The research methode was descriptive, located in Purwakarta district West Java Province, Indonesia, with a sample of 6 Scondary High School (SMP), conducted in 2016. The data collection was done by using a questionnaire enclosed and semi-enclosed and equipped with observation and interviews. Data analyzed with quantitative and qualitative approach to describe and explore with categorization and interpretation. The findings in this study is that the efforts to control deviant behavior of students in Islamic Education in Secondary Schools Purwakarta a control efforts to strengthen control by the students themselves who support the practice of the Islamic religion.